PLANNING AND EXPERIMENTAL STUDIES OF SELECTION THE OPTIMAL WELDING MODE BY THE FRICTION OF FITTING RODS - Buzauova, Toty; Turekhanov , Bayanbek; Mateshov , Arman; Zhauyt, Algazy; Ismagulova, Sarakul; Zhunisbekov, Seitbek (Journal of Applied Engineering Science, 2022)
The methods of friction welding of  various materials have been studied, as well as the design and capabilities of the device for friction welding have been determined. The design of the device for friction welding on the basis of a lathe has been developed taking into account the established requirements and recommendations of machine-building enterprises. To study the influence of technological factors on the quality of welded joint formation, a full factorial experiment (FFE) of type 22 was set up according to the plan. The adequacy of the planned experiment was confirmed by calculations (Fcalcul. = 1.1
Keywords: friction welding, lathe, welding of reinforcement bars, optimal welding modes